A systematic review of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT in the diagnostic value of malignant tumor bone metastasis - Li, Lanying; Hu, Xin; Ma, Jiao; Yang, Songsong; Gong, Weidong; Zhang, Chunyin (Frontiers in Oncology, 2022)
Objective This study aims to perform a systemic analysis of [68Ga]Ga-DOTA-FAPI-04 positron emission tomography (PET)/computerized tomography (CT) and [18F]FDG PET/CT for the diagnosis of malignant tumor bone metastasis based on existing clinical evidence. Methods This systematic review followed the guidelines of the Preferred Reporting Project (PRISMA) for systematic reviews and meta-analysis. This is a retrospective study of articles published in PubMed. Embase was searched online from the start of May 2022. The main endpoints were the maximum standardized uptake value and the tumor-to-background ratio to determine the examination performance of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG for bone transfer stoves. Based on the entry and discharge standards, two researchers extracted documents and data and then performed the quality evaluation. Results A total of eight studies on the metastasis of malignant tumors on bone were included, which involved 358 patients in the final analysis. Conclusion [68Ga]Ga-DOTA-FAPI-04 showed better detection performance for bone metastasis. The sensitivity of [68Ga]Ga-DOTA-FAPI-04 for the diagnosis of the primary tumor was higher than that of [18F]FDG, whereas the specificity of [18F]FDG was higher than that of [68Ga]Ga-DOTA-FAPI-04. However, further randomized controlled trials and prospective clinical trials are warranted to compare the diagnostic performance of [68Ga]Ga-DOTA-FAPI-04 PET/CT and [18F]FDG PET/CT. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier (CRD42022313019)